Studi Pengaruh Konsentrasi Glukosadan Laju Aerasi terhadap Produksi Asam Glukonat oleh Aspergillus niger - Akbarningrum Fatmawati (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Chemical production through fermentation offers advantage in the safe condition used. One of such useful chemical products is gluconic acid, which can be produced by mold Aspergillus niger. This chemical is an interesting product and has various applications. This research studied the effect of initial glucose concentration and aeration rate on the growth of Aspergillus niger FNCC 6098 and its gluconic acid production through fermentation in a batch reactor. The reaction temperature and pH was controlled at 30oC and 6.5, respectively. Initial glucose concentration was varied as 150, 200 and 250 g/L while aeration rate was varied as 1.5, 2, and 2.5 vvm. The concentration of the mold mycelium, gluconic acid product and remaing glucose substrate are presented as function of time. The result of varying initial glucose concentration at fixed aeration showed that the 200 g/L glucose produced the highest yield of gluconic acid. Meanwhile the highest yield of gluconic acid at fixed initial glucose concentration was resulted at aeration rate of 2 vvm.